Associations between competitive anxiety, athlete characteristics and sport context: evidence from a systematic review and meta-analysis - Vedovato Silva Rocha, V.; de Lima Osório, F. (Archives of Clinical Psychiatry, 2018)
Background: There is a vast literature investigating the possible associations between competitive anxiety, athlete variables and sports context. As far as we are concerned, there is no study which has compiled such findings to produce more robust evidence on this topic.